Y = -2x + 5 y =3x - 2
Since both equations are equal to 'y' you can set them equal to each other to solve.
-2x + 5 = 3x - 2 Subtract 3x from both sides
-5x + 5 = -2 Subtract 5 from both sides
-5x = -7 Divide -5 on both sides
x = 7/5
Plug 7/5 back in for x and solve for y.
y = -2(7/5) + 5
y = (-14/5) + (25/5)
y = 11/5
(7/5, 11/5) OR (1.4, 2.2)
Step 2: commutative property of multiplication
Step 3: multiplicative inverse
Step 4: multiplicative identity
Answer: The percent changed because it increased by 180%.
Step-by-step explanation:
Answer:
=-76
hope it is helpful to you ☺️